ATG5 in microglia does not contribute vitally to autoimmune neuroinflammation in mice. Issue 11 (2nd November 2021) - Srimat Kandadai, Keertana; Kotur, Monika B.; Dokalis, Nikolaos; Amrein, Irmgard; Keller, Christian W.; Münz, Christian; Wolfer, David; Prinz, Marco; Lünemann, Jan D.
ABSTRACT: Microglia, resident myeloid immune cells of the central nervous system (CNS), actively shape the circuitry of the brain, maintain CNS homeostasis during the steady state and orchestrate immune responses upon CNS injury. Both canonical and non-canonical functions of the macroautophagy/autophagy-related protein ATG5 regulate myeloid cell survival and immune responses. Here, we report that loss of ATG5 in postnatal microglia does not perturb CNS tissue integrity, microglial cell survival, or immune activation. Learning task performances were unchanged in mutant mice. Furthermore, lack of ATG5 expression in microglia had no impact on the development of experimental autoimmune encephalomyelitis. These data indicate that, basal autophagy, identified to be essential for the survival and function of neuronal cells, is not required to maintain CNS homeostasis if absent in adult microglia and ATG5 expression is dispensable for the development of autoimmune neuroinflammation. Abbreviations Ag, antigen; APC, antigen presenting cell; ATG/ Atg, autophagy-related; CD, cluster of differentiation; CNS, central nervous system; DC, dendritic cell; EAE, experimental autoimmune encephalomyelitis; fl, floxed; LAP, LC3-associated phagocytosis; LC3, microtubule-associated protein 1 light chain 3; MFI, median fluorescence intensity; MHCII, major histocompatibility complex class II; MOG, myelin oligodendrocyte glycoprotein; MS, multiple sclerosis